Understanding experiences of cognitive decline and cognitive assessment from the perspectives of people with glioma and their caregivers: A qualitative interview study - Melissa A. Carlson; Elizabeth A. Fradgley; Christine L. Paul (Elsevier, 2024)
Background: Despite the impact of cognitive decline during brain cancer care, implementing routine cognitive assessment can be challenging. Effective implementation of cognitive assessment necessitates an understanding of implementation from the patient perspective. However, little is known about how people with glioma and their caregivers experience cognitive changes, assessment and support. Objective: To understand the lived experiences of changes in cognition for people with glioma and their caregivers including experiences of: i) perceived or objectively measured cognitive decline (or absence of decline); ii) cognitive assessment following diagnosis, and; iii) met and unmet cognition-related supportive care needs. Design: Semi-structured qualitative telephone interviews were conducted with people with gliomas and support persons and analysed using reflexive thematic analysis. Setting(s): Two Australian cancer services Participants: 18 people with glioma and caregivers Methods: Semi-structured qualitative telephone interviews were conducted with people with gliomas and caregivers and analysed using reflexive thematic analysis. Results: People with glioma (n = 5) and caregivers (n = 13) completed interviews. Four themes were identified: Cognition needs to be considered within the context of glioma diagnosis and treatment; concerns about cognition were initially subordinate to survival but become important; there are challenges identifying and communicating about people with gliomas' changes in cognition; cognition-related supportive care can be helpful but challenging for people with glioma and caregivers to identify and access. Conclusions: Changes to cognition can have considerable impacts of people with glioma and their caregivers which may be overshadowed by treatment and survival. A multi-disciplinary approach to timely cognitive screening, structured referral pathways, and communication with caregivers may provide opportunities for support. Registration: n/a Tweetable abstract: Identifying cognitive changes in people with glioma is important and challenging. A multidisciplinary approach and inclusion of care coordination and caregivers can help.